IDENTITY AND INTERESTS IN EUROPEAN INTEGRATION THEORY: THE INSTITUTIONALIZATION OF THE CFSP - HORIA BARBULESCU (Challenges of the Knowledge Society)
The paper aims to analyze the evolution of the Common Foreign and Security Policy from the stand point of two competing approaches: the intergovernmentalist theory, based on rational institutionalism, and the constructivist theories in integration studies. I also attempt an evaluation of their analytical importance inside the theoretical research concerning CFSP. The contribution of this paper lies in emphasizing that even if interests, material and negotiation power and asymmetrical interdependence are useful starting points in analyzing the potential influence of states on early institutional evolution, power alone does not explain the final outcomes of this evolution or of the policies pursued inside the CFSP.